A Mediation Model of Affective Commitment Towards the Environment On Local Government Employees’ Organizational Citizenship Behaviour Towards the Environment (OCBE) - Ju, Soon-Yew; Diyana, Kamarudin (2023)
Environmental management practices inside an enterprise are related to the environmental citizenship of its personnel. However, not much is covered on the indirect influence that initiates this association. This study delves into whether affective commitment to the environment functions as a mechanism on the interaction between environmental management practices and eco-helping corporate citizenship behaviour among employees. This study was conducted utilising data collected from 244 Peninsular Malaysia local authority employees. 244 employees from municipal councils, city councils and city halls from Peninsular Malaysia were sampled using purposive sampling where the respondents were asked to fill out a questionnaire. Analysis of indirect effects found that affective attachment to the environment serves as a psychological mechanism in the interaction between environmental management techniques and employees' eco-helping organisational citizenship behaviour.